2008
DOI: 10.1021/jf073132l
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Aroma Release of Longjing Tea Infusion: Interaction of Volatile and Nonvolatile Tea Components and Formation of 2-Butyl-2-octenal upon Aging

Abstract: The temporal change in the headspace composition of an aroma model mimicking Longjing green tea aroma was studied in the presence of nonvolatile Longjing green tea constituents. Upon storage at 50 degrees C, the formation of 2-butyl-2-octenal was found, which increased with time. This enal was generated by crotonization of hexanal as demonstrated in model experiments. The formation of 2-butyl-2-octenal was also detected in Longjing tea infusions and Longjing tea leaves upon storage at 50 degrees C. The presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 28 publications
5
50
1
2
Order By: Relevance
“…The chemical odorants observed in our study were quite different from the most active odorants detected in Longjing tea infusions in the previous studies (Kumazawa and Masuda, 1999;Cheng et al, 2008). The difference may be attributed to the different forms of tea aroma used for extraction.…”
Section: Volatile Compounds and Perceived Aroma Qualitycontrasting
confidence: 50%
See 2 more Smart Citations
“…The chemical odorants observed in our study were quite different from the most active odorants detected in Longjing tea infusions in the previous studies (Kumazawa and Masuda, 1999;Cheng et al, 2008). The difference may be attributed to the different forms of tea aroma used for extraction.…”
Section: Volatile Compounds and Perceived Aroma Qualitycontrasting
confidence: 50%
“…Linalool and nonanal have been characterized as aroma-active compounds contributing to floral or fruity odors in Longjing tea infusions (Table 2), and linalool has a high flavor dilution (FD) factor ≥100 (Kumazawa and Masuda, 1999;Cheng et al, 2008). Furthermore, they were also reported to have significant positive correlation with the perceived aroma of Longjing tea or oolong tea (Wang and Ruan, 2009; Wang et al, 2010).…”
Section: Volatile Compounds and Perceived Aroma Qualitymentioning
confidence: 89%
See 1 more Smart Citation
“…This could be explained by the fact that acids are less volatile as compared with the rest of compounds. Most acids identified in this study have previously been reported in green and black teas (Alasalvar et al, 2012;Cheng, Huynh-Ba, Blank, & Robert, 2008;Schuh & Shieberle, 2006). It is well-established that branched-chain acids including 2-and 3-methylbutanoic acids found in tea samples are usually generated from the degradation of branched-chain amino acids.…”
Section: Identification Of Volatile Compounds In Black and Instant Teasmentioning
confidence: 90%
“…Oleic acid와 palmitoleic acid는 n-nonanal, n-nonanol, n-heptanal, 및 n-heptanol의 전구체이다. 일반적으로 오래 된 녹차에서는 1-octen-3-one, hexanal, 및 carbonyl 화합물 농 도는 아주 낮게 나타난다 [17]. 지질분해는 methyl jasmonate, cis-jasmone, 및 jasmine lactones등을 생성한다.…”
Section: Lipidunclassified